Age-Dependent Enhancement in Fecundity and Ova Diameter of Schizopyge niger (Heckel, 1838) in Dal Lake, Kashmir: Reproductive Potential in Schizothoracids - Ifrah Rashid; Tasaduq H. Shah; Farooz A. Bhat; Adnan Abubakr; Bilal A. Bhat; Ahali Jahan (Fishery Technology, 2024)
Understanding the reproduction and recruitment pattern is essential for successful conservation of a species. Accurate estimates of fecundity plays a crucial role in comprehending fish population dynamics. The snowtrout, Schizopyge niger, is a Cyprinid fish widely distributed throughout the lakes of Kashmir valley and is one of the most important commercial fish species. In this study, we examined the age-dependent reproductive perfor- mance of female S. niger, aiming to gain insights into its breeding characteristics for the development of an optimal brood-stock management plan. The study involved 78 female S. niger specimens collected from Dal Lake during the spawning season, representing age groups of 2+, 3+, 4+, 5+, and 6+ years. Fecundity and ova diameter showed an increasing trend from age 2+ (3,971 eggs; 1.45 mm) to age 6+ (10,501 eggs; 2.00 mm). Total fecundity exhibited positive correlations with age, total weight, ovary weight, and ova diameter. Additionally, there was a positive correlation between ova diameter and fish age, with the highest fecundity and largest ova diameter observed in the 6+ years age group. Among each age group, fecundity and ova diameter varied significantly (p <0.05). Based on these findings, for optimal broodstock management of S. niger, it is recommended to use females of the 6+ years age group after assessing the quality of eggs.